Teori Keadilan Kontemporer (Sebuah Kajian Teori Hukum) - La Ode Muhammad Iman Abdi Anantomo Uke (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
Studying the science of law can not be separated by the existence of legal theory. The term theory comes from the English language theory, and in Dutch theorie. Theory also comes from the word